Should Colours be Protected by Trade Mark Law? - Cox, Tiffany (Kent Law Review, 2014)
The significance of colour as an invaluable marketing tool and source of brand differentiation provides support both for and against its protection by trade mark law. Despite the advantages afforded by trade mark protection, this article demonstrates that such protection is undesirable in a capitalist market that is supposed to foster freedom of competition. Colour depletion will unduly restrict the ability of newcomers to develop their own brand identity as the limited availability of colours will diminish with increased registration. Problems of shade confusion will hasten the depletion of colours and hinder the ability of the courts to properly determine the scope of protection afforded to a colour trade mark. By looking at the complications in administering a system of colour trade mark protection and the unfair competition associated with the monopolisation of colours, this article will conclude that colours should not be protected by trade mark law.